Effects of Tire Inflation Pressure and Load on Predicted Pavement Strains - Dae-Wook Park; Amy Epps Martin; Jin-Hoon Jeong; Seung-Tae Lee (The Baltic Journal of Road and Bridge Engineering)
In this paper, effects of tire loads and inflation pressures on predicted pavement responses were presented. The objective was to study the effect of increased tire loads and tire inflation pressures on predicted transverse strains and vertical strains at the different pavement layers and material properties. A 3 dimensional (3D) tire contact stresses for 6 different tires were interpolated from the database of the measured tire contact stresses. The shape of measured tire contact stresses is dependent on tire loading conditions. The results show that the predicted values were different near the asphalt concrete (AC) layer by increased tire inflation pressure. Under the increased tire load, the predicted values were different at the base and subgrade layer. From statistical analysis, predicted transverse strains at the bottom of asphalt layer and vertical strains at the top of subgrade are affected by different AC thicknesses, AC moduli, and subgrade moduli.